2009
DOI: 10.1159/000236047
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Sonic Hedgehog Signaling Pathway in Olfactory Neuroblastoma

Abstract: Objectives: Sonic hedgehog (Shh) signaling pathway is associated with tumor development; however, the role of Shh signaling in the development of olfactory neuroblastoma (ONB) is unknown. This study aimed to investigate the relationship between the regulation of Shh signaling and the pathogenesis of ONB. Methods: The expression of Shh signaling components was characterized by immunohistochemistry in human non-tumor olfactory epithelium and ONB specimens, and by RT-PCR and immunoblotting in human ONB cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 40 publications
1
23
0
1
Order By: Relevance
“…Given that EWSR1-FLI1 promotes NKX2-2 expression by upregulating GLI1, 30 NKX2-2 positivity in olfactory neuroblastomas may be explained by tumoral activation of sonic hedgehog signaling. 31 Mesenchymal chondrosarcomas, characterized by HEY1-NCOA2 gene fusion, 32 demonstrated immunoreactivity for NKX2-2 in 33% of cases in a prior study 11 and, in this study, …”
Section: Discussionsupporting
confidence: 57%
“…Given that EWSR1-FLI1 promotes NKX2-2 expression by upregulating GLI1, 30 NKX2-2 positivity in olfactory neuroblastomas may be explained by tumoral activation of sonic hedgehog signaling. 31 Mesenchymal chondrosarcomas, characterized by HEY1-NCOA2 gene fusion, 32 demonstrated immunoreactivity for NKX2-2 in 33% of cases in a prior study 11 and, in this study, …”
Section: Discussionsupporting
confidence: 57%
“…Taken together, our results lead us to assume that sonic hedgehog signaling is activated in neuroblastoma, although few studies support a role for Shh signaling in the tumorigenesis of neuroblastoma [48,66]. In our study, we were able to determine some of the target genes of Shh- Sample NT-1 shows unmethylation (a), NT-8 shows hemi-methylation (b), and NT5 shows methylation (c) in the HHIP promoter region GLI1 signaling.…”
Section: Discussionmentioning
confidence: 64%
“…Experimental studies demonstrated the Sonic hedgehog signaling pathway (Shh) being activated in ONB [78]. The influence of Shh signaling on the expression of its signaling components and cell cycle-related regulators was determined by immunoblotting and quantitative RT-PCR.…”
Section: Potential Targetable Pathwaysmentioning
confidence: 99%